Fingolimod (FTY720), a Sphinogosine-1-Phosphate Receptor Agonist, Mitigates Choroidal Endothelial Proangiogenic Properties and Choroidal Neovascularization - Christine M. Sorenson; Mitra Farnoodian; Shoujian Wang; Yong-Seok Song; Soesiawati R. Darjatmoko; Arthur S. Polans; Nader Sheibani (Cells, 2022)
Neovascular or wet age-related macular degeneration (nAMD) causes vision loss due to inflammatory and vascular endothelial growth factor (VEGF)-driven neovascularization processes in the choroid. Due to the excess in VEGF levels associated with nAMD, anti-VEGF therapies are utilized for treatment. Unfortunately, not all patients have a sufficient response to such therapies, leaving few if any other treatment options for these patients. Sphingosine-1-phosphate (S1P) is a bioactive lipid mediator found in endothelial cells that participates in modulating barrier function, angiogenesis, and inflammation. S1P, through its receptor (S1PR1) in endothelial cells, prevents illegitimate sprouting angiogenesis during vascular development. In the present paper, we show that, in choroidal endothelial cells, S1PR1 is the most abundantly expressed S1P receptor and agonism of S1PR1-prevented choroidal endothelial cell capillary morphogenesis in culture. Given that nAMD pathogenesis draws from enhanced inflammation and angiogenesis as well as a loss of barrier function, we assessed the impact of S1PR agonism on choroidal neovascularization in vivo. Using laser photocoagulation rupture of Bruch’s membrane to induce choroidal neovascularization, we show that S1PR non-selective (FTY720) and S1PR1 selective (CYM5442) agonists significantly inhibit choroidal neovascularization in this model. Thus, utilizing S1PR agonists to temper choroidal neovascularization presents an additional novel use for these agonists presently in clinical use for multiple sclerosis as well as other inflammatory diseases.